A large-scale viability assessment of the potato cryobank at the International Potato Center (CIP) - Vollmer, R.; Villagaray, R.; Cárdenas, J.; Castro, M.; Chavez, O.; Anglin, Noelle L.; Ellis, David (Springer, 2017)
The International Potato Center (CIP) in Lima, Peru, maintains the global in-trust collection of cultivated potato. The material from this collection is distributed worldwide on request for research, breeding, and education under the auspices of the International Treaty for Plant Genetic Resources for Food and Agriculture (ITPGRFA, http://www.fao.org/plant-treaty/en/) (FAO 2009). The 4388 accessions in this collection are maintained in vitro to ensure that once cleaned of viruses, the germplasm remains virus free and can move freely across international borders without introducing disease(s) to other countries. While in vitro maintenance safeguards the material from infection, it requires a large number of resources to maintain an in vitro collection of this size.